Upaya Warga GG. Subur, Bandar Selamat dalam Menjaga Kebersihan Lingkungan - Adhita Naya (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The community service activity themed “Efforts of the GG. Subur, Bandar Selamat Residents in Maintaining Environmental Cleanliness” was carried out to increase public awareness in maintaining the cleanliness of the surrounding environment, as well as to encourage active participation in preserving environmental sustainability. This program includes household waste management, street park cleaning, and mosque cleanliness. The methods used were socialization about the importance of maintaining environmental cleanliness, mutual cooperation in cleaning the environment, and interactive discussions with local residents to explore ideas on efficient waste management methods. The results of the activity showed a positive response from the community, with active involvement in every stage of the activity, as well as the emergence of initiatives to continue the cleanliness program independently through a mutually agreed upon routine schedule of gotong royong. This program not only increases awareness about the importance of cleanliness but also strengthens social relationships among residents and fosters a sense of ownership over the environment. In conclusion, this activity successfully raised the community’s awareness of environmental cleanliness and is expected to continue as a sustainable community-based environmental management model.